2015
DOI: 10.1016/j.aller.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Tear and serum vitamin D levels in children with allergic rhinoconjunctivitis

Abstract: To our knowledge, this is the first reported study to show an association between serum 25-hydroxycholecalciferol and ARC in a childhood group. Higher levels of serum 25-hydroxycholecalciferol in children with allergic rhinoconjunctivitis may indicate a possible aetiopathogenic mechanism in the development of allergic rhinoconjunctivitis. This is also the first report to examine tear fluid vitamin D levels in paediatric ARC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
2
11
1
1
Order By: Relevance
“…The present data show that the serum levels of VitD3 are significantly lower in AR patients than that in healthy controls. Similar condition was also reported by others in AR patients , allergic conjunctivitis , and asthma . Besides allergic disorders, VitD3 abnormality was also found associating with rheumatoid arthritis , diabetes , and cancer .…”
Section: Discussionsupporting
confidence: 89%
“…The present data show that the serum levels of VitD3 are significantly lower in AR patients than that in healthy controls. Similar condition was also reported by others in AR patients , allergic conjunctivitis , and asthma . Besides allergic disorders, VitD3 abnormality was also found associating with rheumatoid arthritis , diabetes , and cancer .…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, we have shown that 25-hydroxyvitamin D can be measured in human tears by competitive chemiluminescent immunoassay and that the 25-hydroxyvitamin D levels were significantly higher in the tears than in the serum. Similarly, another study reported significantly higher 25-hydroxyvitamin D levels in tears (71.8 ± 6.2 ng/ml) compared to serum (21.8 ± 11.3 ng/ml) in children (12.5 ± 2.5 years) using electro chemiluminescent immunoassay [22]. The difference in the 25-hydroxyvitamin D levels between tear fluid and serum seem to vary between the current study and that reported by Goksugur SB et al The primary reason underlying this difference could be related to the principle and sensitivity of the assay used to measure 25-hydroxyvitamin D [23, 24].…”
Section: Discussionmentioning
confidence: 98%
“…In a study it was found that the 25-hydroxyvitamin D level was significantly higher in the tears than in the serum [18]. Also in, another study reported significantly higher 25-hydroxyvitamin D levels in tears (71.8 ± 6.2 ng/ml) compared to serum (21.8 ± 11.3 ng/ml) in children (12.5 ± 2.5 years) using electro chemiluminescent immunoassay [19]. .…”
Section: Discussionmentioning
confidence: 95%